1997
DOI: 10.1007/s004420050058
|View full text |Cite
|
Sign up to set email alerts
|

The effects of elevated CO 2 atmospheres on the nutritional quality of Eucalyptus foliage and its interaction with soil nutrient and light availability

Abstract: Seedlings of Eucalyptus tereticornis (Smith) were grown under two levels of availability each of CO (352 and 793 µmol mol), soil nutrients (1/24 and 1/4 Hoagland's solution) and light (full and 30% sunlight). Low soil nutrient availability or high light increased the C:N ratio of leaves, leading to lower leaf nitrogen concentrations, higher leaf specific weights and higher levels of both total phenolics and condensed tannins. These results were consistent with other studies of the effect of environmental resou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
126
4
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(139 citation statements)
references
References 30 publications
8
126
4
1
Order By: Relevance
“…3b) is at odds with the findings of several other studies of both total phenolics and condensed tannins (e.g. Waterman et al 1984, Hartley et al 1995Lawler et al 1997;Koricheva et al 1998). These studies found a decrease in carbon-based compounds, which they attributed to the lower overall energy and carbon supply from photosynthesis in shaded plants.…”
Section: Discussionmentioning
confidence: 83%
“…3b) is at odds with the findings of several other studies of both total phenolics and condensed tannins (e.g. Waterman et al 1984, Hartley et al 1995Lawler et al 1997;Koricheva et al 1998). These studies found a decrease in carbon-based compounds, which they attributed to the lower overall energy and carbon supply from photosynthesis in shaded plants.…”
Section: Discussionmentioning
confidence: 83%
“…Extra C can also be diverted to secondary metabolites (Pen4 uelas et al, 1996 ;Lawler et al, 1997) and\or re-emitted as volatile compounds (Seufert et al, 1995 ;Johnson & Allen, 1996), which may be more convenient than the investment in stemwood in semi-arid environments such as the Mediterranean. This has also been observed for Quercus species at the Bossoleto CO # spring (Johnson et al, 1997).…”
Section: mentioning
confidence: 99%
“…In addition, genetic variability provides raw material to gain an understanding of the potential evolutionary consequences of elevated CO # , to select for optimal genotypes, or to analyse the range of variation in CO # response independently of phylogenetic differences. It is also expected to alter plant-herbivore interactions (Fajer et al, 1989 ;Lawler et al, 1997) and decomposition processes (Cou# teaux et al, 1991 ;Cotrufo et al, 1994).…”
Section: mentioning
confidence: 99%